Put your heart on the page : plotting to enrich your back story. - Hinds, Diane M.; Perry, Anne; Entertainment Bureau Ltd; Soundview Media Partners ([London, England] : The Entertainment Bureau Ltd, 2015)
Following on from the successful film An Introduction To Writing, comes the second in the series, aimed at helping the aspiring writer to navigate the complex world of adding plots within their story so that it carefully reveals certain information needed to build storylines and characters.
Narrator: Anne Perry.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Creative writing; Plots (Drama, novel, etc.); Fiction -- Authorship; Fiction -- Technique; Authorship; Instructional films; Nonfiction films; Internet videos; Streaming video